3 D-hierarchically structured MnO2 for catalytic oxidation of phenol solutions by activation of peroxymonosulfate: Structure dependence and mechanism - Wang, Yuxian; Sun, Hongqi; Ang, Ming; Tade, Moses; Wang, Shaobin (Elsevier BV, 2015)
Hierarchical materials have facilitated fascinating applications in heterogeneous catalysis due to that micro-sized bulk is easily separable and nano-sized sub-blocks can significantly enhance catalytic performance. In this study, corolla-like δ-MnO2 with sub-blocks of nanosheets, and urchin-shaped α-MnO2 with sub-blocks of nanorods were synthesized by a simple hydrothermal route. The hydrothermal temperature significantly influenced the crystal structure, morphology and textural structure of the obtained three-dimensional (3D) MnO2 catalysts. The catalytic activities of three samples prepared at 60, 100 and 110 °C (denoted as Mn-60, -100 and -110, respectively) were thoroughly evaluated by activation of peroxymonosulfate (PMS) for catalytic oxidation of phenol solutions. Based on first-order kinetics, the rate constants of Mn-60, -100 and -110 catalysts were determined to be 0.062, 0.132, and 0.075 min−1, respectively. The activation energy of Mn-100 in catalytic oxidation of phenol solutions was estimated to be 25.3 kJ/mol. The catalytic stability of Mn-100 was also tested and discussed by monitoring Mn leaching. Electron paramagnetic resonance (EPR), quenching tests, total organic carbon (TOC) analysis and identification of intermediates were applied to illustrate the activation processes of PMS and the mechanism of phenol degradation.